1999
DOI: 10.2337/diacare.22.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Emerging epidemic of type 2 diabetes in youth.

Abstract: This review considers the epidemiologic evidence of an increasing incidence of type 2 diabetes in youth, the classification and diagnostic issues related to diabetes in young populations, pathophysiologic mechanisms relevant to the increasing incidence, the role of genetics and environment, and the community challenge for prevention and treatment. Type 2 diabetes in youth has been recognized to be frequent in populations of native North Americans and to comprise some 30 percent of new cases of diabetes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
480
0
30

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 889 publications
(521 citation statements)
references
References 0 publications
11
480
0
30
Order By: Relevance
“…23,31 The mortality in children without critical illness admitted to general pediatric wards is significantly lower. 30 In agreement with the increasing rate of obesity among children with diabetes, 32,33 especially in minority populations, we found that hospitalized children with a history of diabetes and glucose >180 mg/dL had a higher body mass index than those with normoglycemia (P < .001). Obesity in children has been associated with the presence of several comorbidities and an increased risk of hospital complications.…”
Section: Discussionsupporting
confidence: 79%
“…23,31 The mortality in children without critical illness admitted to general pediatric wards is significantly lower. 30 In agreement with the increasing rate of obesity among children with diabetes, 32,33 especially in minority populations, we found that hospitalized children with a history of diabetes and glucose >180 mg/dL had a higher body mass index than those with normoglycemia (P < .001). Obesity in children has been associated with the presence of several comorbidities and an increased risk of hospital complications.…”
Section: Discussionsupporting
confidence: 79%
“…It cannot be accepted that OA, which is known as a disorder of old age, will in the future be increasingly diagnosed among adolescents, like type 2 diabetes is now (45) .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Affected young people are typically grossly obese, have reached puberty, and have a family history of type 2 diabetes; in more developed countries, many belong to minority ethnic groups. 1,2 The young age at presentation exposes these patients to a high risk of long-term complications. 1 Progression from normal glucose tolerance to overt type 2 diabetes in adults involves an intermediate stage of IMPAIRED GLUCOSE TOLERANCE, referred to as prediabetes.…”
Section: Introductionmentioning
confidence: 99%